Hubungan Kuantitatif Struktur-Aktivitas dan Desain Senyawa Novel Phenyl Benzimidazoles sebagai Penghambat Wnt/?-Catenin untuk Terapi Pancreatic Ductal Adenocarcinoma: Quantitative Structure-Activity Relationship and Design of Novel Phenyl Benzimidazoles as Wnt/?-Catenin Inhibitors for Pancreatic Ductal Adenocarcinoma Therapy - Dwi Syah Fitra Ramadhan; Rusli Rusli; Taufik Muhammad Fakih (Jurnal Sains dan Kesehatan, 2023)
In the pancreatic ductal adenocarcinoma (PDAC) initiation and progression, the Wnt/β-Catenin signaling pathway showed a very important role. Earlier study showed that novel phenyl benzimidazoles have inhibiton activity in Wnt/?-Catenin pathway. The purpose of the present study was to design novel phenyl benzimidazoles as a Wnt/?Catenin inhibitor on PDAC based on the Quantitative In the pancreatic ductal adenocarcinoma (PDAC) initiation and progression, the Wnt/?-Catenin signaling pathway showed a very important role. Earlier study showed that novel phenyl benzimidazoles have inhibiton activity in Wnt/?-Catenin pathway. The purpose of the present study was to design novel phenyl benzimidazoles as a Wnt/?Catenin inhibitor on PDAC based on the Quantitative Structure Activity Relationship (QSAR) method. The molecule structures were built optimized by semi empirical AM1 using Gaussian. 12 Descriptors were selected which represented electronical, hydrophobic, and steric parameters using MOE 2014.0901. The compounds suspected as an outlier were then removed from the data set based on XZ-score value, i.e. compounds with XZ-score above 2.5. The data set were then classified into two parts, i.e. training set and test set. Validation was performed using Leave One Out (LOO) method and F test. The new derivatives were designed using topliss scheme, in which parent compound with the lowest IC value was used as a 50 template. The statistical analysis showed that there were two most influential descriptors of Wnt/?-Catenin inhibition activity: mr and LogS. The LOO validation gave Q2 = 0.7363. Six new derivatives, predicted to have lower IC that of parent compound. Keywords: Benzimidazoles, PDAC, QSAR, Wnt/?-Catenin Abstrak Jalur pensinyalan Wnt/?-Catenin sangat penting dalam inisiasi dan perkembangan dari pancreatic ductal adenocarcinoma (PDAC). Studi sebelumnya menunjukkan bahwa fenil benzimidazol baru memiliki aktivitas penghambatan di jalur Wnt/?-Catenin. Tujuan dari penelitian ini adalah untuk merancang fenil benzimidazol baru sebagai penghambat Wnt/?Catenin pada PDAC berdasarkan metode Hubungan Kuantitatif Struktur-Aktivitas (HKSA). Struktur molekul dibangun dan dioptimalkan dengan metode AM1 semi empiris menggunakan Gaussian. Sebanyak 12 Deskriptor dipilih yang mewakili parameter elektronik, hidrofobik, dan sterik menggunakan MOE 2014.0901. Senyawa-senyawa yang diduga outlier kemudian dikeluarkan dari kumpulan data berdasarkan nilai XZ-score, yaitu senyawa-senyawa dengan XZ-score di atas 2,5. Kumpulan data kemudian diklasifikasikan menjadi dua bagian, yaitu training set dan test set. Validasi dilakukan menggunakan metode statistik Leave One Out (LOO). Turunan baru dirancang menggunakan skema topliss, dimana senyawa induk dengan nilai IC terendah digunakan sebagai template. Analisis statistik menunjukkan bahwa ada dua deskriptor paling berpengaruh dari aktivitas penghambatan Wnt/?-Catenin: mr dan LogS. Validasi LOO menunjukkan niali Q2 = 0,7363. Enam turunan baru, diprediksi memiliki IC yang lebih rendah dari senyawa induknya. Kata Kunci: Benzimidazoles, PDAC, HKSA, Wnt/?-Catenin